Asking about sex and growing up : a question-and-answer book for boys and girls - Cole, Joanna; Tiegreen, Alan (New York : Morrow Junior Books, 1988)
Uses a question-and-answer format to present sex information for preteens.
Includes index.
Bibliography: p. 6-7.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
5.5
Keywords: Sex instruction for children -- Miscellanea; Questions and answers; Sex instruction for children; Questions and answers; Sex education